2019
DOI: 10.1186/s12917-019-2072-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymerase spiral reaction assay for the visible molecular detection of porcine circovirus type 3

Abstract: Background Porcine circovirus type 3 (PCV3) is a newly emerging circovirus that might be associated with porcine dermatitis and nephropathy syndrome, reproductive failure, and cardiac and multisystemic inflammation. To aid the prevention and control of the infectious disease caused by PCV3, we developed a novel isothermal amplification assay using polymerase spiral reaction (PSR), which allows the visual detection of preserved strains and clinical samples. Results This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Further, polymerase spiral reaction (PSR), also an isothermal amplification assay based on PCV3 Cap gene, has been described. The PSR assay, run at 62 • C for 50 min, detected PCV3 at LOD 1.13 × 102 copies/μl with phenol red and cresol red (Ji et al, 2019).…”
Section: Othersmentioning
confidence: 99%
“…Further, polymerase spiral reaction (PSR), also an isothermal amplification assay based on PCV3 Cap gene, has been described. The PSR assay, run at 62 • C for 50 min, detected PCV3 at LOD 1.13 × 102 copies/μl with phenol red and cresol red (Ji et al, 2019).…”
Section: Othersmentioning
confidence: 99%
“…The serological tests, developed on the basis of indirect enzyme immunoassay, allowed conducting the retrospective study on PCV-3 in the pig population in China which demonstrated an increase in the number of PCV-3-positive cases from 22.35 to 51.88 % in three years (Deng J et al, 2018), and the examination of the population of sows at the farms of China, the results of which demonstrated the spreading with the seroprevalence more than 50 % (of PCV-3 among both clinically healthy sows and the animals with reproductive failures (Zhang S et al, 2019). Some studies showed, that (Q) PCR is more effective for PCV-3 diagnostics in compare to serological methods or in situ hybridization (Kedkovid R et al 2018 At present, PCV-3 detection is mostly based on the use of molecular genetic methods using different PCR formats (Rodrigues ILF et al, 2018;Fux R et al, 2018;Liu Y et al, 2019;Dal Santo AC et al, 2020) and amplifi cation technologies (Ji J et al, 2019;Ye X et al, 2018;Zheng S et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reaction system can be carried out at a constant temperature of 60 • C and completed within 30 min, and the results can be visually judged by the real-time detection system or using a smartphone-based cassette (19). The test can save 20 min compared with novel polymerase spiral reaction (20), 40 min compared with real-time loop-mediated isothermal amplification (15), and at least 60 min compared with qPCR or PCR (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that this method had good specificity, with no cross false reaction with other porcine viral pathogens. Most isothermal amplification techniques use color change (4,20) or turbidity (17) to interpret the results, but P-S-MCDA monitors the amplification of the target gene in real time quantitatively by the real-time PCR detection system. Therefore, the P-S-MCDA not only avoids the error of visual interpretation of the results but also is capable of quantitative analysis of target gene sequences.…”
Section: Discussionmentioning
confidence: 99%